Modification of Rice Thresher-Hammer Thresher Type - Ahmad Harbi; Tamrin -; Warji -; Budianto Lanya (The University of Lampung, 2012)
The thresher rice has developed in previous research is instrument thresher rice type hammer thresher. But the threshing not going well, Where rice stalk is still difficult to get out of the thresher. The objective of this research is to modify machine type paddy thresher hammer . Modification is conducted by adding director channel in upper wall of threshing chamber and to change straw exiting channel near the feeder with size of 15 cm width and 19 cm height. By this method, paddy straw is expected to exit from threshing chamber and threshing process can run smoothly. Methods used is Modification tools, testing modification result, observation and data collection. Observations are made to percentages of threshed paddy grain, percentage of unthreshed paddy grain, good threshed paddy grain, percentage of damaged threshed paddy grain, threshing duration, and working capacity of the machine per hour. Keywords: Thresher rice, thresher rice type hammer, modify machine thresher.